Racial discrimination campaigns during the reign of Muhammad ibn Tumart and their role in consolidating the Almohad movement in Moroccan society 518-519 AH / 1124-1125 AD - ورده زينب (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
Islamic history witnessed a process of repetition of the phenomenon of the advent of a person who calls for a return to the correct religion, unification of the nation around it, resorting to Sharia law, raising the slogan of enjoining good and forbidding evil, and jihad for the sake of God. And he began calling people to return Islam to its first state, and despite the essence of Ibn Tumart’s religious call, it soon turned into a political call, and succeeded in establishing a major state in the Arab and Islamic Maghreb, and extended until it included Andalusia. The emergence of the Almohad movement, and its success in establishing a major state, led to the emergence of movements opposing the existing political authority, so Ibn Tumart and his successor rulers sought to adopt a new approach, based on the process of distinction and differentiation, or what was called campaigns of recognition, and this matter became a doctrinal and political phenomenon, It ended with the consolidation of Almohad rule, after relying on political extremism based on exclusion, and therefore this process does not distinguish the spiritual side of religion from the ideological or political side of it. Keywords: Muhammad ibn Tumart, the Mahdi, the Arab and Islamic Maghreb, the process of discrimination, recognition campaigns.